If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + -4) = y Reorder the terms: 5(-4 + y) = y (-4 * 5 + y * 5) = y (-20 + 5y) = y Solving -20 + 5y = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -20 + 5y + -1y = y + -1y Combine like terms: 5y + -1y = 4y -20 + 4y = y + -1y Combine like terms: y + -1y = 0 -20 + 4y = 0 Add '20' to each side of the equation. -20 + 20 + 4y = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 4y = 0 + 20 4y = 0 + 20 Combine like terms: 0 + 20 = 20 4y = 20 Divide each side by '4'. y = 5 Simplifying y = 5
| 2x^2=91 | | 3x+12+2x=15 | | y=-2(4)+7 | | 3(x+7)-9=4x+12 | | 7b+3c-2b-3c= | | 16x+32=-14x-6 | | 3x+6=2x-9 | | X+(x*0.2)=8000 | | 3(2x-5)=8x-7 | | 72-6=6-8x | | 10a+14b+3c+2a= | | x*(x*0.2)=8000 | | 4x+9+3x+12=56 | | 3z+1=0 | | 7(9+3x)=294 | | 7(2x-1)=15 | | 0.05x+y+5z=100 | | 3ln^2x=0 | | 3x^2+4y^2-6x+8y-5=0 | | X+x+4+2x+8=180 | | x+x+4+2x+8= | | 4x^3-34x=0 | | 15+-5x=125 | | 15+-5=125 | | -7m+9=39-2m | | 8(3m-4)-10m= | | p-17=-54 | | 4x^2+x^2=1156 | | 4.158=0.00002x+0.07352 | | 40158=0.00002x+0.07352 | | 4.707=0.00002x+0.07352 | | 12x+3(4x+8)=12x+3*4x |